HUBUNGAN STATUS EKONOMI DENGAN PENGGUNAAN ALAT KONTRASEPSI SUNTIK - Yossi Wijayanti (Universitas Muhammadiyah Pringsewu, 2015)
Indonesia is a developing country that has many of total population. In Indonesia the most used contraceptive is the type of injectable contraceptive, as much as 46,87. One of factor that affect use contraceptive is economic status. The purpose of the study was to know the relationship economic status with use injectable contraceptive. This study is survei analiic research approach Cross Sectional. The samling tecnique used is total sampling. The sampel size were 63 respondents who acceptors in BPS Wiji Lestari Pandan Surat Pringsewu Tahun 2015. Corelation hypotesis cesting is using Chi Square analisis. Result of the analysis showed p value (0,649) α (0,05) which means that Ho is be accepted. Value obtained Odd Ratio (OR) 0,675. The conclusion there is nothing significant relationship beetwen economic status whit use injectable contaceptive.Suggestion : Based on the result it is expected that healt services can increase quality of healt service in preventive and promotive eforts on tools and efective contraceptive and appropriate state of sociate, especially in terms of economic.